2010
DOI: 10.3324/haematol.2010.029769
|View full text |Cite
|
Sign up to set email alerts
|

SQSTM1-NUP214: a new gene fusion in adult T-cell acute lymphoblastic leukemia

Abstract: Letters to the Editor © F e r r a t a S t o r t i F o u n d a t i o n

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

2
42
0

Year Published

2011
2011
2024
2024

Publication Types

Select...
6
3
1

Relationship

0
10

Authors

Journals

citations
Cited by 31 publications
(44 citation statements)
references
References 9 publications
2
42
0
Order By: Relevance
“…[22][23][24][25][26] Mutations of the SQSTM1 gene have been detected in patients with both sporadic and familiar Paget disease of the bone, 27 and protein accumulation can be seen in several different human tumors. 28,29 Oncogenic rearrangements are rare and single-case reports have been described with a nucleoporine gene (SQSTM1-NUP214) in a patient with acute lymphoblastic leukemia 30 and with ALK (SQSTM1-ALK) in a case of ALK-LBCL. 10 However, the true incidence of the SQSTM1 rearrangement in lymphomas might be underestimated if not evaluated by FISH analysis or rearrangement studies; notably conventional cytogenetic abnormalities could be misleading and show a t(2;5) (p23.1;q34.2) chromosomal translocation similar to that of the common NPM-ALK rearrangement, given the close location of NPM and SQSTM1 genes close to the telomere end of chromosome 5.…”
Section: Discussionmentioning
confidence: 98%
“…[22][23][24][25][26] Mutations of the SQSTM1 gene have been detected in patients with both sporadic and familiar Paget disease of the bone, 27 and protein accumulation can be seen in several different human tumors. 28,29 Oncogenic rearrangements are rare and single-case reports have been described with a nucleoporine gene (SQSTM1-NUP214) in a patient with acute lymphoblastic leukemia 30 and with ALK (SQSTM1-ALK) in a case of ALK-LBCL. 10 However, the true incidence of the SQSTM1 rearrangement in lymphomas might be underestimated if not evaluated by FISH analysis or rearrangement studies; notably conventional cytogenetic abnormalities could be misleading and show a t(2;5) (p23.1;q34.2) chromosomal translocation similar to that of the common NPM-ALK rearrangement, given the close location of NPM and SQSTM1 genes close to the telomere end of chromosome 5.…”
Section: Discussionmentioning
confidence: 98%
“…Mutations of these genes have been reported in haematological malignancies, e.g. SQSTM1-NUP214 gene fusion in cases of T-cell acute lymphoblastic leukaemias (ALL), but not in AML (Gorello et al, 2010). In addition, our study identified potential novel coding mutations in MAP3K1 ( MEKK ), MAP3K6 ( MEKK6 ), EP300 ( p300 ), and WDR90 (Table SI).…”
mentioning
confidence: 99%
“…We identified several novel cryptic gene rearrangements including intergenic deletions involving NOTCH1/EDF1 and GATA2/DNAJB8, as well as translocations leading to the rearrangements of SQSTM1-NUP214 and IGH-BCL2. Mutations of these genes have been reported in hematologic malignancies, for example the SQSTM1-NUP214 gene fusion in cases of T-cell acute lymphoblastic leukemias (ALL), but not in AML 16 .…”
Section: Resultsmentioning
confidence: 99%